Pendugaan Populasi Harimau Sumatra dan Satwa Mangsanya di Taman Nasional Bukit Barisan Selatan - Gunardi Djoko Winarno; Revi Ameliya (Fakultas Biologi | Universitas Jenderal Soedirman, 2009)
Bukit Barisan Selatan National Parks has been given a named by World Heritage Committee as The Tropical Rain Forest of Sumatra (The World Heritage site) in July 2004 in Shozou China. However, many of Bukit Barisan Selatan National Park’s forest have already been wrecked by irresponsible people. Illegal logging is a big problem in Bukit Barisan Selatan National Parks. Indonesian’s forests are home to megabiodiversity in the world, but deforestation has caused a lengthening list of the inhabitant species to be classified as endangered. For example, the Sumatran tiger has a category to be an appendix I species by Convention on International Trade in Endangered Species (CITES).The decline of a species is very often a strong indicator of degradation in the local habitat, which can also negatively impact the biodiversity of that area. Perhaps the greatest threat to the survival of the tiger is destruction of its habitat. With the expansion of human populations, the logging of forests, the elimination of natural prey, and the spread of agriculture, there is continuation of destruction toward Sumatran tiger population. Monitoring the Sumatran tiger and its prey using camera trap can provide a data base on the continuity of the Sumatran tiger population management.